USEFULNESS OF PARS PLANA VITRECTOMY IN MANAGING ASYMPTOMATIC EYES OF EALES` DISEASE - Ishaq, Mazhar; Niazi, Muhammad Khizar (Journal of Ayub Medical College Abbottabad, 2003)
Background: Eales` disease is an idiopathic obliterative vasculopathy that commonly affects the peripheral retina of healthy young males characterized by recurrent vitreous haemorrhage. We did this study to evaluate the usefulness of Pars Plana vitrectomy in asymptomatic eyes of patients presenting with Eales` Disease. Methods: Fifty-five patients with Eales` Disease demonstrable on the basis of three mirror fundus exam and Florescein Fundus Angiography with vitreous hemorrhage underwent either Pan retinal photocoagulation or vitrectomy in a span of 3 years. Their fellow asymptomatic eyes were initially treated with laser photocoagulation and after being followed for six months, they were grouped into either progressive cases (Group A) comprising of eleven eyes that underwent early vitrectomy, or non-progressive cases (Group B) comprising forty-four eyes that did not undergo any further treatment. These cases were followed for at least three years (range 38-42 months). Results: Out of the eleven eyes of group A, seven (63.63%) showed regression of disease process as compared to only ten out of forty-four eyes (22.72%) in Group-B. Conclusion: Early vitrectomy in established cases of Eales` disease provides satisfactory results and helps in preventing complications, which are difficult to treat. Regular checkup of peripheral retina by triple mirror examination should be performed in all asymptomatic fellow eyes of Eales` disease to detect the disease process at an early stage and prevent further complications. KEYWORDS: Eales` disease, Retinal neovascularization, Retinal vasculitis, Vitreous hemorrhage, Vitrectomy